Two new species of cave crickets Endecous (Notoendecous) Gorochov, 2014 (Orthoptera: Grylloidea: Phalangopsidae) from northeastern Brazil - Castro-Souza, Rodrigo Antônio; Zefa, Edison; Ferreira, Rodrigo Lopes (Zootaxa, 2017)
The current work presents the description of two Brazilian new species of the subgenus Endecous (Notendecous) Gorochov, 2014 recorded for the states of Rio Grande do Norte and Bahia, Northeastern Brazil. The morphology of phallic complex was used as main criterion for distinguishing the two species. Furthermore, aspects on the natural history, intraspecific variation and a pictorial key are presented considering the species known for this subgenus.